Growth and condition index of pokea clams (Batissa violacea var. celebensis, von Martens 1897) in Lasolo River Mouth, Southeast Sulawesi - Bahtiar; Permatahati Yustika Intan; Ishak Ermayanti; Fekri Latifa (E3S Web of Conferences, 2023)
The somatic growth and condition index (CI) of pokea population aren’t yet fully known in the Lasolo river. This research aims to decide the somatic growth relationship between length and weight as well as the condition factor of pokea population. This research was carried out in the Lasolo river from January-December 2014. Pokea clams were taken from the river bed with traditional tool (tangge). The length and total weight of the clams were determined by employing a caliper with a precision of 0.5 cm and a digital scale with an accuracy of 0.01g. Meat and shells were then dried in an oven at 70°C about 48 hours. The dry weight of the meat and the shells of the pokea clams were weighed using a digital scale with an accuracy of 0.0001 g. Calculations obtained average b parameter values of the males and females about 2.52 and 2.70, respectively. The b values for both sex of clams were 2.37-3.05 and 2.24-3.15, respectively, which were within the negative allometric category. The CI values of the male (3.98±1.44) and female (4.27±1.52) putting them in the fat category. The condition index experienced three local peak periods in February-March, June, and November-December.